The Legal Analysis Regarding The Responsibility Of Business Actors For Hidden Defects In Used Car Sale And Purchase Agreements - Ardiansyah Ardiansyah; Erniwati Erniwati; Aidil Fitri (Jurnal Multidisiplin Dehasen (MUDE), 2026)
The activity of buying and selling used cars will certainly begin with an agreement between the two parties which is stated in the contents of the agreement. An agreement is a legal relationship that occurs between two or more parties who agree to do something. An agreement is an event where someone promises to another person or where two people promise each other to do something. The limits of the agreement are regulated in Article 1313 of the Civil Code which states that an agreement is an act in the name of one or more people binding themselves to one or more other people. The problem in this thesis is how the business actor is responsible for hidden defects in the used car sale and purchase agreement and what are the legal sanctions for the business actor if there is an element of intent for hidden defects in the used car sale and purchase agreement. The type of research that the author uses is normative juridical supported by empirical research. Normative juridical research is a method that focuses on research on library data, or secondary data through legal principles and comparative law. The conclusion in this thesis is that the responsibilities of used car business actors are regulated in Articles 19, 24, 25 and 26 of Law No. 8 of 1999 concerning Consumer Protection and the factors causing hidden defects in used car sales are negligence of the seller, lack of consumer knowledge, inability to check, fraud or deception and incomplete agreements.